Suppression of P2X4 and P2X7 by Lactobacillus rhamnosus vitaP1: effects on hangover symptoms - Jeong Eun Kwon; Woojae Hong; Hyelin Jeon; Cha Soon Kim; Hyunggun Kim; Se Chan Kang (AMB Express, 2024)
Abstract This study aimed to identify substances including Lactobacillus rhamnosus vitaP1 (KACC 92054P) that alleviate hangover-induced emotional anxiety and liver damage. The association between emotional anxiety caused by hangover and the genes P2X4, P2X7, SLC6A4 was investigated. In vitro and in vivo analyses were conducted to assess the influence of free-panica on alcohol-induced upregulated gene expression. Additionally, the concentration of AST, ALT, alcohol, and acetaldehyde in blood was measured. Free-panica, consisting of five natural products (Phyllanthus amarus, Phoenix dactylifera, Vitis vinifera, Zingiber officinale, and Lactobacillus rhamnosus), were evaluated for their regulatory effects on genes involved in alcohol-induced emotional anxiety and liver damage. The combination of these natural products in free-panica successfully restored emotional anxiety, and the concentration of AST, ALT, alcohol, and acetaldehyde in blood to those of the normal control group. These findings support the potential development of free-panica as a health functional food or medicinal intervention for relieving hangover symptoms and protecting liver from alcohol consumption.